2018
DOI: 10.1016/j.ijmedinf.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Rubber stamp templates for improving clinical documentation: A paper-based, m-Health approach for quality improvement in low-resource settings

Abstract: The use of templates improves paper-based documentation of patient care, a first step towards improving the quality of care. Rubber stamps provide a simple and low-cost method to print templates on demand. In combination with ubiquitously available mobile phones, information entered on paper can be easily and rapidly digitized. This 'frugal innovation' in m-Health can empower small, private sector facilities, where large numbers of urban patients seek healthcare, to generate digital data on routine outpatient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…The Guidelines Adherence in Slums Project has pioneered the use of rubber stamp templates and smartphones to deliver routine data on primary care delivery in low-resource settings. A previous publication described improvements in clinical documentation for non-communicable diseases 23. This paper first demonstrates improved documentation of care for common infectious conditions.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…The Guidelines Adherence in Slums Project has pioneered the use of rubber stamp templates and smartphones to deliver routine data on primary care delivery in low-resource settings. A previous publication described improvements in clinical documentation for non-communicable diseases 23. This paper first demonstrates improved documentation of care for common infectious conditions.…”
Section: Discussionmentioning
confidence: 80%
“…The Guidelines Adherence in Slums Project aimed to test the usability, acceptability and effectiveness of paper-based clinical documentation tools in improving quality of outpatient care in private sector PHCs serving the urban informal settlements of Nairobi, Kenya 23. While usability and acceptability were assessed using qualitative tools (manuscript in preparation), this paper focuses on effectiveness of the intervention in improving quality of clinical documentation and care.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar improvements have been reported in studies that have assessed the effect of audit and/or educational interventions on clinical record keeping in other disciplines. [49][50][51][55][56][57] Consistent with these findings, Bowie et al (2012) suggested placing education at the centre of clinical audit enhanced the effectiveness of the process. 58…”
Section: Efficacy Of Clinical Auditmentioning
confidence: 82%